Hamlet - Shakespeare, William, 1564-1616.; Gill, Roma. (New York : Oxford University Press, 1992)
Presents the text of the play, students' notes, historical background, a brief biography of Shakespeare, and a complete list of his plays.
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism, interpretation, etc; English drama